A dinâmica urbana de cidades médias do interior paulista sob o Estatuto da Cidade - Terci, Eliana Tadeu; Otero, Estevam Vanale; Goulart, Jefferson Oliveira [UNESP] (My University, 2013)
The paper examines the scope of the Statute of the City as a new regulation act of Brazilian urban policy based on the comparative study of contemporary processes in three medium-sized cities in São Paulo State (Piracicaba, Bauru and Rio Claro). The study analyzes three complementary dimensions: economic, urban and politicalinstitutional. It observes the existence of endogenous and exogenous obstacles, which have been conditioning urban policies and hindering the implementation of the directives of newly approved Master Plans. Despite the expressive incorporation of instruments of the Statute of the City, many of them has neither been implemented nor regulated. That scenario can be generalized as prevalent in Brazil and refers to contemporary standards of regional and urban development

O artigo examina o alcance do Estatuto da Cidade como novo marco regulatório da política urbana brasileira a partir de estudo comparativo de processos contemporâneos em três cidades médias do interior paulista (Piracicaba, Bauru e Rio Claro). O estudo se faz mediante a análise de três dimensões complementares: econômica, urbanística e político-institucional. São constatados obstáculos endógenos e exógenos que têm condicionado as políticas urbanas e di cultado a aplicação dos indicativos dos Planos Diretores recém-aprovados. Apesar da expressiva incorporação formal dos instrumentos do Estatuto da Cidade, boa parte não tem sido implantada ou não foi regulamentada, cenário que pode ser generalizado como predominante no país e que remete aos padrões contemporâneos do desenvolvimento regional e urbano.
Keywords: Urban dynamics; Medium-sized cities; Statute of the city; Participative master plans; Dinâmica urbana; Cidades médias; Estatuto da cidade; Planos diretores participativos